Andrew Gitari - Kabaune village, Giaki - Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Andrew Gitari is a farmer and a former teacher. He talks in the video about the environmental impact of both cutting down trees and the importance trees have in bringing rain and water. However, it needs to be the right trees, and not the types that demand a lot of water themselves. Nowadays fruittrees are grown in the area.